SEJARAH AL-QUR’AN : Telaah Atas Sejarah Sab’u Qirā‘at dalam Disiplin Ilmu - Rumi Chafidhoh; Kholila Mukaromah (QOF, 2017)
The seven qira’at al-Qur’an cannot be ignored in the study of the science of exegesis. It is then called sab’u qira’at. But in the journey there was a misunderstanding of understanding between sab’u qiraat with sab’atu aḥruf. After doing some analysis on the history of sab’u qiraat and the traditions used as the basis of qira’at law, it can be known the difference result of both. The popularity of sab’u qiraat was initiated by a tabi’in named Abu Bakr Ahmad ibn Musa bin ‘Abbas bin Mujahid (d. 334 H). Besides sab’u qiraat which has degrees mutawattir in qira’at science, there is also qira’at ‘asyirah and qira’at’ arba’ah ‘asyar. The purpose of this study is to know the history of sab’u qira’at to become a discipline that stands alone as well as to provide an understanding of the difference sab’atu aḥruf and sab’u qira’at. Therefore, the author used critical text analysis. The result is to find a more comprehensive understanding of the difference between sab’atu aḥruf and sab’u qira’at as well as the history of sab’u qira’at formation into a discipline.